Advances in fracture research, (fracture 81) : proceedings of the 5th International Conference on Fracture (ICF5), Cannes, France, 29 March-3 April 1981 - Francois, D. (International series on the strength and fracture of materials and structures., 1982)
Advances in Fracture Research, Volume 6, documents the proceedings of the 5th International Conference on Fracture (ICF5) held in Cannes, France, 29 March-3 April 1981. The conference was attended by 670 participants from 26 countries. The program consisted of plenary sessions with invited speakers, technical sessions with contributed papers, a poster session, and two round table discussions. This volume contains 14 papers that deal with topics such as advancements in fracture mechanics; the application of fracture mechanics in three areas: damage tolerance requirements for aircraft structures.